KUTÓ-KUTÉ PERSONAL PRONOUN - Muhammad Muhammad (Prasasti: Journal of Linguistics)
Forms, meanings, dialects, and characteristics of Sasak language Pronouns were discussed by Nurhadi (1996), Sukmawati, (2004) and Riadatul Jannah  (2004). Hence this research paper describes a social factors, personal pronoun, and how Bayan speakers communite with. Alternatively it would  like to focus on socio-cultural factors of Bayan personal pronouns. This ethnographical research gathered the information from the informants in a Bayan community in north Lombok, west Nusa Tenggara, and Indonesia. The informants were selected in terms of their age, mobile and their speaking Indonesia ability. The language practice was observed and the informants were in-depth interviewed. Personal pronoun sentences were analysed by employing a referential identity method with deviding-key-factors techniques. Bayan people communicate pronouns in three ways: raden-tomenak-to-jajarkarang, jajarkarang-to-menak-to-raden and raden. menak. jajarkarang. They apply various speaker, addressee and object personal pronouns, e.g. aku, tiang, titiang and dawekdiq, kamu, epe, sida, pelinggih, and pelungguh. pragayan, and bataŋan, iya, nya, e. Communicating amongst same stratification, they commonly consider ages, position, and status. However social relation, and gender seemed not to indicate an effect on personal pronoun application.